Strategi Kesantunan Bahasa pada Ulasan Konsumen di Marketplace GoFood dalam Konteks Komunikasi Digital - Siswanto, Siswanto; Arsul, Muhamad Rizki; Mursida, Mursida; Dwiyanti, Elsa (J-LELC: Journal of Language Education, Linguistics, and Culture, 2025)
The development of digital technology has created new opportunities for socio-economic interaction, one of which is through consumer reviews on online food applications such as GoFood. This study aims to describe the strategies and principles of politeness in consumer reviews on GoFood. Using a descriptive pragmatic qualitative approach, 100 reviews were selected purposively and analysed using the theories of Brown & Levinson (1987), Culpeper (2011), Herring (2013), and Leech's (2014) politeness principles. The results show variations in the use of politeness strategies. Within the Brown & Levinson framework, Bald on Record dominated (31 utterances), indicating a tendency towards a straightforward style. In Culpeper's strategy, Withhold Politeness (32 utterances) appeared most frequently, showing that criticism was conveyed passively or without politeness markers. Herring's analysis showed that Interaction (41 utterances) was most dominant, confirming the function of reviews as a means of building social relationships. Meanwhile, Leech's principle is dominated by Agreement Maxim (35 utterances), reflecting the influence of a collectivist culture that emphasises agreement and harmony. Overall, GoFood reviews are characterised by a direct and interactive communication style, but are still influenced by Indonesian cultural politeness values that maintain solidarity and social harmony.